Mode-Dependent Loss Equalized Few-Mode Fiber Photonic Lantern - Yingxuan Li; Senyu Zhang; Zhiyong Zhao; Jing Liu; Zhuyixiao Liu; Ming Tang (IEEE Photonics Journal)
We propose and fabricate an unconventional photonic lantern that is not only able to achieve mode multiplexing and demultiplexing, but also has the functionality of mode-dependent loss equalization. In the process of fusion splicing between the tail fiber of photonic lantern and the few-mode fiber, by controlling the fusion splicing parameters, a refractive index (RI) modified waveguide is formed at the fusion splicing region, through which the fundamental mode will have higher attenuation than the higher-order modes, which enables us to control the attenuation of different modes, so that we can customize the unconventional photonic lantern with different differential mode attenuation (DMA). Simulation has been carried out to investigate the dependence of DMA on the structure of the RI modified waveguide, and experiments have been implemented to investigate the dependence of DMA on discharge parameters, which matches well with the simulated tendency. In addition, CCD measurements of all three output ports have been performed on the fabricated devices, well-defined mode field patterns and high mode purity at the C-band can be observed. The proposed novel unconventional photonic lanterns open a new way to obtain simultaneous mode multiplexing / demultiplexing and mode-dependent loss equalization function, which will be greatly beneficial in the few-mode fiber transmission system.